Analisis Kohesi Leksikal dalam Cerita Pendek Karya Halima Khatun "No One Ever Asks Mum" - Aisyahida, Namira; Asidiky, Zakie; Puspa, Vindy Melliany (Jurnal SORA - Pernik Studi Bahasa Asing, 2024)
This study analyzed the types of lexical cohesion and measured the degree of cohesiveness in “No One Ever Asks Mum,” a short story by Halima Khatun. It used Brian Paltridge’s theory of lexical Cohesion within the framework of Discourse Grammar and Scinto’s Formula, employing a qualitative descriptive method. The data for this study were collected through a documentation-collecting technique involving browsing and selecting the short story from Google Books. The chosen story consists of 67 paragraphs and 670 sentences, which are classified based on the types of lexical cohesion. The findings reveal the presence of 15 repetitions, 7 synonymy, 12 antonymy, 18 meronymy, 16 hyponymy, and 6 collocations in the short story. Additionally, the research also assesses the degree of cohesiveness in the short story using Scinto’s Formula, resulting in a score of 110,44%. This high percentage indicates a strong level of cohesiveness, indicating that the cohesive lexical devices employed by the author effectively contribute to the overall flow and coherence of the narrative.